“I fear I am not in my perfect mind.” Jan Klata’s King Lear and the Crisis of Europe - Cieślak, Magdalena (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
In his Shakespearean productions Jan Klata tends to radically experiment with sets, texts, and contexts. He puts the plays in culturally and politically specific locations, experiments with bi- or multilingual productions, and incorporates other texts into the Shakespearean frame. In this way, he uses Shakespeare as a means to address contemporary problems and tensions that are vital for his geopolitical reality, exploring the issues of national identities, the cultural legacy of Europe and its nations, as well as past conflicts and present crises. Klata’s King Lear (Narodowy Teatr Stary, Kraków, 2014), set in the religious context of the Catholic Church and using mostly Polish language, with only decorative additions in foreign languages, does not engage in European politics with the same directness and force as his earlier productions. And yet, as I wish to argue, this performance is also strongly concerned with European identity, and may, therefore, be seen as a valid voice in the discussion on how Shakespearean productions help to understand our current-day reality.